2005
DOI: 10.1148/radiol.2342040013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease: Thin-Section CT Measurement of Airway Wall Thickness and Lung Attenuation

Abstract: Bronchial wall measurements differ between patients who have COPD with CB and those who have COPD without CB. The correlation between airway dimensions and indexes of airway obstruction in patients with COPD and CB indicates that the bronchial tree is the site of anatomic-functional alterations in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 25 publications
2
145
2
4
Order By: Relevance
“…The CT measurement of airway wall dimensions was estimated to play a front-line role in the study of COPD because airway remodelling represents the major reason for airflow limitation [17][18][19]21]. In our study, bronchial wall thickening was diagnosed approximately as often in chest radiography (58%) as in CT (64%) and-similar to other investigations [27]-as a major finding.…”
Section: Tobacco Burden and Dirty Chestsupporting
confidence: 84%
See 1 more Smart Citation
“…The CT measurement of airway wall dimensions was estimated to play a front-line role in the study of COPD because airway remodelling represents the major reason for airflow limitation [17][18][19]21]. In our study, bronchial wall thickening was diagnosed approximately as often in chest radiography (58%) as in CT (64%) and-similar to other investigations [27]-as a major finding.…”
Section: Tobacco Burden and Dirty Chestsupporting
confidence: 84%
“…The pathological entity of smokeinduced RB-ILD is also called ''smokers' bronchiolitis'' as it is seen almost exclusively in current or former smokers. While numerous publications have investigated the CT appearance of emphysematous changes of the lung parenchyma [16,17] or alterations of the bronchial walls [18][19][20][21], less attention has been directed to the abnormalities of chest radiographs caused by chronic bronchitis or RB-ILD.…”
Section: Discussionmentioning
confidence: 99%
“…20 Airway dimensions were measured using the method described in previous studies 21,22 with a modification. The cross-section of the right B1 bronchus, which appeared on the HRCT film was scanned, and the images were magnified 50 times for the following measurements.…”
Section: Analysis Of Airwaysmentioning
confidence: 99%
“…COXSON et al [95] measured all cross-sectioned airways and reported a similar result in a large group of obstructed index patients and their smoking siblings, and, in addition, observed that the airway and parenchymal phenotypes showed familial concordance, suggesting that the susceptibility to develop emphysema or airway disease is heritable. Recently, ORLANDI et al [96] found that patients with COPD who have chronic bronchitis have increased airway wall thickening in comparison with more severely obstructed patients without chronic bronchitis. Conversely, COPD patients without chronic bronchitis had a more significant decrease in lung attenuation.…”
Section: Airway Imaging In Copdmentioning
confidence: 99%